The Distributional Effects Associated with Land Finance in China: A Perspective Based on the Urban–Rural Income Gap - Zixing Wang; Meirong Zhang (Land, 2023)
Land finance has become an important way of generating fiscal incomes in developing countries, while the urban–rural income gap (URIG) in developing countries remains high. However, existing research has not paid much attention to the connection between land finance and the URIG. Therefore, this study used a fixed-effects model to test this relationship for 275 prefecture-level cities in China from 2014 to 2017. To identify the effects of the potential omitted variables, this study conducted additional robustness checks using placebo tests. The results showed that land finance significantly widened the URIG, and this finding was maintained after a set of tests. Further study found that the effect of land finance on the URIG showed significant heterogeneity. Land grants by tender, listing, and auction significantly widened the URIG, while land grants by agreement did not affect the URIG; the effect of land finance on the URIG was more significant in Eastern and Middle regions, but not marked in Western regions; and land finance had no impact on the URIG in large and medium-sized cities, while it had a significant impact in small cities. Based on the above results, this study offers recommendations to improve land fiscal policy and urban-biased development strategies, which aim to promote the equalization of the basic rights and interests of urban and rural residents and reduce the URIG.